Mental disorders among terrorists and mass murderers: a comparative study - Trimbur, Margot (Handbook of understanding terrorism, 2024)
Terrorism and mass murder are two forms of violence that have become international concerns in the twenty-first century. Despite their apparent differences, they share some similarities. This chapter aims to compare and contrast the two phenomena by examining their definitions, global impact, and the psychological profiles of terrorists and mass murderers. This chapter presents a comparative study of the psychological profiles of terrorists and mass murderers. Two systematic literature reviews were carried out to investigate mental disorders in these two populations. It examines the role of mental disorders in both populations and discuss their potential relationship with violent behavior. The case of Anders Behring Breivik, who perpetrated the 2011 terrorist attacks in Norway, is used to illustrate the complex interplay between terrorism, mass murder, and psychiatry. Finally, the chapter addresses the role of mental health professionals in understanding and preventing terrorism and mass murder, as well as the limitations of current research and the need for a dynamic and multidisciplinary approach to address these complex issues.